Encountering the state through legal tenure security: Perspectives from a low income resettlement scheme in urban India. (15th December 2016) - Patel, Kamna
Highlights: Legal tenure systems enable state control over who lives where and how, with legitimacy. In Ahmedabad, state control over low income citizens is exerted through fear. State control is incomplete encouraging the renegotiation of tenure rules by citizens. Empirical findings in Ahmedabad problematize advocacy for legal tenure security. The findings conceptualise the relationship between state power and legal tenure security. Abstract: Tenure security systems—which determine who lives where and under what terms and conditions—are processes of governance that make and effect the relationship between those who confer tenure security and those on who tenure security is conferred. Yet, in dominant analyses of land and housing tenure security, and in policy recommendations for property rights and legal tenure security in developing countries, governance implications are overlooked in favour of analyses of the relative merits of different tenure systems mainly in terms of security, livelihood and economic impact. Using interview data and observations from a resettlement scheme in Ahmedabad, India, this paper empirically examines citizen-state relations in the context of a major shift from de facto (in practice) to legal tenure security and asks how do citizens who have recently come to live under legal tenure security encounter the state and make sense of it. I find a bureaucracy of tenure security that exerts control over low income citizens largely through fear. However, such control is incomplete and acts of resistance suggest an emerging 'paralegal' space to renegotiate tenure rules. I conclude by examining the findings through a conceptual framework that explains the relationship between state power and legal tenure security. I also discuss the need for greater scrutiny of the political effects of urban land and housing tenure systems on poor people.